ANALISIS PENGELOLAAN UTANG PT. TIRTA MAHAKAM RESOURCES,TBK PERIODE 2011 – 2013 - RINA MASITHOH HARYADI, YENY PUJI ASTUTI. TITIN RULIANA. (EKONOMIA, 2016)
In general, companies use their own capital as the permanent capital of the foreign capital is only used as a supplement if the necessary funding is insufficient. However, debt is a very important source of funding for companies, particularly those with limited capital itself. Many companies in Indonesia that make loans to Banks and other financial institutions. PT. Tirta Mahakam Resources, Tbk is one of the companies that use foreign capital (debt). Based on this background, the problems in this thesis is